"(NpROBLEMI )QÆNFORMATIKI TA KOMP(B'(N@TERNOÇ TEHNÆKI(B" ((Npækt(B-2014), (NmÆVNAR(B. (NNAUK(B.-(NPRAKT(B. (NKONF(B.s)E (III ; 2014 ; (N~ERN)QÆWCÆ(B). (NpROBLEMI ÆNFORMATIKI TA KOMP(B'(N@TERNOÇ TEHNÆKI (B((Npækt(B-2014) : (NPRACÆ (BIII-Ç (NmÆVNAR(B. (NNAUK(B.-(NPRAKT(B. (NKONF(B. (27-30 (NTRAW(B., 2014 (N~ERNÆWCÆ(B) = (NpROBLEMY INFORMATIKI I KOMPX@TERNOJ TEHNIKI (B((Npikt(B-2014) : (NTRUDY (BIII-(NEJ mEVDUNAR(B. (NNAU^(B.-(NPRAKT(B. (NKONF(B. (27-30 (NMAQ(B, 2014 (N~ERNOWCY(B) = Informatics and computer technics problems (PICT-2014) : proc. of the Third Intern. Conf. (27-30 may, 2014 Chernivtsi, Ukraine) /s)E - "(NpROBLEMI )QÆNFORMATIKI TA KOMP(B'(N@TERNOÇ TEHNÆKI(B" ((Npækt(B-2014), (NmÆVNAR(B. (NNAUK(B.-(NPRAKT(B. (NKONF(B.s)E ((N~ERN)QÆWCÆ(B:s)E 2014; (NsOPRON@K(B, (Nf(B. (No(B.s; (NrUSNAK(B, (Nm(B. (Na(B.s; (NwALX(B, (No(B. (Nd(B.s; )Qæ(NN(B-(NT KÆBERNETIKI ÆM(B. (Nw(B. (Nm(B. (NgLU[KOWA nan uKRAÇNI(B.s)E; (NkI)QÇWSXKIJ NAC(B. (NUN(B-(NT ÆM(B. (Nt(B. (N{EW^ENKA(B.s)E; (NnAC(B. (NTEHN(B. (NUN(B-(NT uKRA)QÇNI (B"(Nkpæ(B".s)E; (N~ERN)QÆW(B. (NNAC(B. (NUN(B-(NT ÆM(B. (N`RÆQ fEDXKOWI^A(B.s)E ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2014)
(NwIDANNQ M)QÆSTITX PRACÆ U^ASNIKÆW (BIII-Ç (NmÆVNARODNOÇ NAUKOWO(B- (NPRAKTI^NOÇ KONFERENCÆÇ (B"(NpROBLEMI ÆNFORMATIKI TA KOMP(B'(N@TERNOÇ TEHNÆKI (B"((Npækt(B- 2014), (NQKA PROHODILA NA BAZÆ ~ERNÆWECXKOGO NACÆONALXNOGO UNÆWERSITETU ÆMENÆ `RÆQ fEDXKOWI^A(B.s)E
(Nb)QÆBLÆOGR(B. (NW KÆNCÆ ST(B.s)E
(NuKR(B., (NROS(B. (NTA ANGL(B. (NMOWO@s
Keywords: (NkOMP(B'(N@TERI(B.s; (N~ERN)QÆWECXKIJ AWTOR(B.s)E